Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

(m^-4/3)^1/4 divided by m^0 n^3/4(m^-3/2 n^2)

Sagot :

[tex]\frac{(m^{-\frac{4}{3}})^{\frac{1}{4}}}{m^{0}(m^{-\frac{3}{2}}n^{2})} = \frac{m^{-\frac{1}{3}}}{m^{-\frac{3}{2}}n^{2}} = \frac{m^{\frac{3}{2}}}{m^{\frac{1}{3}}n^{2}} = \frac{m^{\frac{7}{6}}}{n^{2}} = \frac{\sqrt[6]{m^{7}}}{n^{2}} = \frac{\sqrt[6]{m^{6} * m}}{n^{2}} = \frac{\sqrt[6]{m^{6}}\sqrt[6]{m}}{n^{2}} = \frac{m\sqrt[6]{m}}{n^{2}} [/tex]